THE EVALUATION OF TOURISM DESTINATION BRAND EQUITY FROM THE FEMALE TOURIST'S PERSPECTIVES (STUDY OF 16 CITIES IN IRAN) - Mohammad KAZEMI; Mehdi HESAM; Majid Saeidi RAD; Mehdi CHERAGHI (Geo Journal of Tourism and Geosites, 2018)
Despite the surge in interest in research on tourism destinations, little attention has been paid to investigating and comparing destination brand equity that implies conceptualizing how tourists evaluate a destination brand is complex. This study examined empirical information to compare and identify the status of destination brand assets of 16 Iranian cities. In recent years feminist tourism is largely neglected in Iran, accordingly the present study aims at evaluating the status of the tourism destination brand equity from the female tourists’ perspective in several cities in Gilan province, northern Iran. The statistical population of the study consists of the total number of female tourists visiting different cities in Gilan province. However, regarding the large statistical population, the sample size was determined using random sampling and 380 female tourists were chosen from the population. Since women tend to be more precise and accurate than men in visual fields and accordingly in evaluating a destination, we decided to use a female population in this study. Data were collected by questionnaires measuring variables such as awareness, mental image, perceived quality and loyalty. The data analysis were conducted using SPSS through cluster analysis and logistic regression tests. The results indicate that the status of the tourism destination brand equity in this region is promising; besides, the image of brand was the most influential and the dimension of loyalty was the least influential in promoting the tourism destination brand equity in this region.